DIGITAL FORMULATION OF BUSINESS STRATEGIES IN THE TOURISM SECTOR USING 7S MCKINSEY AND WEB-BASED - Lishobrina, Lina Fatimah; Ramdhani, Ade Yanyan; Haya, Hindun Afni Al (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The tourism industry in Indonesia, including Purbalingga, has significant potential as a rapidly growing economic sector. Renowned for its natural beauty, cultural richness, and diverse tourist destinations, Indonesia attracts visitors globally. Purbalingga, in Central Java, offers various attractions such as scenic hills, rivers, waterfalls, historical temples, and rich local traditions, providing a unique tourism experience. However, despite its potential, Purbalingga's tourism industry faces challenges like suboptimal infrastructure, ineffective promotion, and the need for human resource development in tourism services. Developing and strengthening the tourism industry at national and local levels, like Purbalingga, is essential to maximize Indonesia's economic, social, and cultural potential. The urgency lies in adapting to the digital era, especially during the COVID-19 pandemic, which has highlighted the importance of online presence for promotion and distribution.Methods: This study aims to analyze the alignment between D'Las' business goals and the McKinsey 7S Framework components, and to design a suitable digital strategy for the tourism sector. Results: Results show that applying the McKinsey 7S Framework through digital platforms is highly effective in formulating strategies for business digitalization. The framework supports improvements in both hard skills and soft skills, enabling D’Las to optimize internal operations, strengthen service quality, and expand market reach. Furthermore, the outcomes include the formulation of concrete and measurable digital strategies, potential Intellectual Property Rights (IPR), and contributions to academic knowledge through publication in a nationally accredited journal. This research provides practical guidelines for SMEs in tourism to adopt digital strategies that strengthen competitiveness and long-term business sustainability. Keywords: Digital Business Strategy Formulation, Tourism, 7S McKinsey